"Magic Bullet": Eccentric Macular Hole as a Complication from Dexamethasone Implant Insertion. (5th October 2016) - Christensen, Logan; Sanders, Riley; Olson, Jeffrey
Abstract : Introduction . Intravitreal drug injections and implants are generally safe but do carry some risk, from both the procedure itself and adverse effects of the medications. We report a case of an eccentric macular hole after dexamethasone implant (Ozurdex®) administration. Ex vitro force testing was performed to evaluate dexamethasone implant injection force. Methods . Five dexamethasone implant (Ozurdex) applicators were placed 16 mm from a force plate and the force of the injected dexamethasone pellet was recorded in Newtons. Four dexamethasone implant applicators were placed 16 mm from a force plate in a basic saline solution and the force of the pellet was recorded. Results . Average maximum force in air was 0.77 N and 0.024 N in a basic saline solution (BSS). Conclusion . We present a case report of an eccentric macular hole after dexamethasone implant administration. We hypothesize a mechanical injury to the retina during insertion caused the macular hole. Force testing done in air demonstrated sufficient force from the pellet injection to cause retinal damage though injections done in BSS showed reduced forces.